THE YOUNG PEOPLE OF THE STATE COMMUNITY SERVICE OF THE YOUNG PEOPLE OF BANGGAI LAUT, CENTRAL SULAWESI - Jufrin H. Jalaman (Jurnal Abdisci, 2026)
Abstract Background. The role of young people is an important to a village's sustainability, because whether a village is good or not depends on how they play a role in it. Method. The only way in the 4.0 Era at this time is to collaborate as a method of community service. Results. Boasting the Sea with its rich historical, cultural, and natural potential makes it a complete package for a civilization. With the spirit of building from the village, where the village is the reality of what happens there, it describes the face of a city. A good Potential, Problem, and Response approach is a parameter in this service. Conclusion. The tagline of the program "Ko-Ba-Tong-Ba-Tong" Co-Education, Ba-Counseling, Tong-kaji, Ba-Tourism, and Tong Pe-History aims to attract common attention, stimulate and increase sensitivity to thinking in society, and knit the idea of change with action in the regional context.